Caracterização, ecotoxicologia e uso de substratos oriundos de resíduo de abatedouro de suínos para produção de mudas cítricas - Ramires, Maiara Figueiredo (2019)
Pork has been the most consumed animal protein in the world and production levels are significantly higher in comparison to other livestock activities. However, this scenario of expansion in the sector also generates large quantities of waste, which are often improperly disposed in agricultural areas, causing environmental imbalance. The aim of this thesis was to obtain information about the toxicity of pig slaughterhouse waste on earthworms (Eisenia andrei) and lettuce (Lactuca sativa L.), radish (Raphanus sativus L.) and rice (Oryza sativa L.) as bioindicators, in addition to characterizing the potential of the waste as a substrate for the production of citrus rootstock Poncirus trifoliata (L.) Raf. In order to do this, the study was conducted in three stages. Firstly, to prepare treatments for the later stages, pig slaughterhouse waste was subjected to composting (aerated and natural) and vermicomposting, except for the in natura treatment, which was evaluated fresh. Thus, the treatments were pig slaughterhouse waste in natura (PSWin); pig slaughterhouse waste after aerated composting (PSWa); pig slaughterhouse waste after natural composting, without the turning of the pile (PSWn); pig slaughterhouse waste after vermicomposting (PSWv). The second stage consisted of chemical, physical and biological characterization, as well as ecotoxicological characterization. This was done through phytotoxicity tests with lettuce, radish and rice and Eisenia andrei earthworms using acute and chronic toxicity tests, in addition to a set of enzyme biomarkers. In the third stage, the treatments consisted of different percentages of PSWin, PSWa, PSWn and PSWv and soil, in addition to a treatment with commercial substrate (Carolina Soil®) for the production of Poncirus trifoliata (L.) Raf. citrus rootstock seedlings. Biometric measurements were carried out and macro and micronutrient contents were determined in shoot dry weight of the rootstock. One of the most noteworthy findings was that pig slaughterhouse waste has satisfactory chemical and physical characteristics for use as substrate, especially after stabilization processes, which allowed and favored the development of Poncirus trifoliata (L.) Raf., regardless of the percentage of waste used, although increasing percentages of the waste were more efficient in meeting the macro and micronutrient demands of the citrus rootstock seedlings. From an ecotoxicological perspective, pig slaughterhouse waste in natura and after composting showed greater toxicological potential to the environment than waste after vermicomposting. This suggests that pig slaughterhouse waste needs to undergo a more advanced stabilization process of decomposition prior to soil application.